ENVIRONMENTAL ANALYSIS AND ALFAMART BUSINESS STRATEGY - Agus Tamrin Reni; Della Jane Wijaya; Verina (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This study aims to determine the condition of the retail business in Indonesia by analysing the environment and business strategy of Alfamart. In this study, using a literature review, Data collection was carried out by means of interviews, direct observation, and documentation. The analytical technique used to analyse Alfamart's business environment and strategy is the analysis of 1) Directional Strategy, 2) Portfolio Strategy, and 3) Parenting Strategy. The results of Alfamart's environmental analysis and business strategy are: 1) directional strategy analysis: Alfamart has succeeded in proving its target achievement with the number of outlets reaching 16,492 by the end of 2021. Alfamart can obtain a wider target audience because online shopping methods are easy and can be accessed anywhere. 2) Strategy Portfolio Analysis: Alfamart Company has the potential to gain market share and enter the stars category when its sales exceed those of its competitors; and 3) Parenting Strategy: implementation of the parent company strategy that has been applied to subsidiaries in terms of corporate funding and the determination of investment and development.